Locus Coeruleus Malfunction Is Linked to Psychopathology in Prodromal Dementia With Lewy Bodies - Hansen, Niels (Frontiers in Aging Neuroscience, 2021)
Background: The locus coeruleus (LC) is a nucleus in the human brainstem with a variety of noradrenaline-driven functions involved in cognition, emotions, and perception. Dementia with Lewy bodies (DLB) constitutes a neurodegenerative disease involving deposits of alpha-synuclein, first appearing in the brainstem. The goal of this narrative review is to delineate the relationship between the expression of psychiatric symptoms as an early-onset of DLB and the degeneration of the LC’s noradrenaline system. Methods: We searched in PubMed for relevant articles concerning LC degeneration and psychiatric symptoms in prodromal DLB in this narrative review. We rely on the McKeith criteria for prodromal psychiatric DLB. Results: We found four studies that document neuronal loss, deposits of Lewy bodies and other hints for neurodegeneration in the LC in patients with DLB. Furthermore, we reviewed theories and studies on how the degenerated noradrenaline LC system contributes to psychiatric DLB’s phenotype. We hypothesized how anxiety, hallucinations, delusions, and depressive symptoms might occur in DLB patients due to degenerated noradrenergic neurons entailing consecutive altered noradrenergic transmission in the LC’s projection areas. Conclusions: LC degeneration in prodromal DLB might cause psychiatric symptoms as the first and non-motor manifestation of DLB, as the LC is affected earlier by degeneration than are dopaminergic structures such as the substantia nigra, which are impaired later in the disease course.